Private sector and NGOs scale AWD with target of 50,000+ farmers in Bangladesh - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The Christian Commission for Development in Bangladesh (CCDB), an institutional member of northwest Focal Area Network (FAN) established under this project, committed to take more ambitious actions to promote the adoption of AWD among CCDB's more than 50,000 farmer-members. Additionally, a new project on "Introducing Water Efficient Technology to Barind Tract" is being implemented with AWD as its flagship technology. From the combined initiatives on AWD outscaling, FAN received an international award for Innovation in Behavioural Change.